Competences for collaboration and knowledge sharing in digital society - a case study with an erasmus intensive programme - Messias, Inês (2018)
With the advent of social and collaborative environments, students became more active and participative - they not only have access to contents but also create and share them, becoming proactive. Communication has evolved, and with this evolution came the new media and the possibility of live conferencing, video sharing, social networking, collaborative tools, allowing the student to create, work collaboratively and communicate in a more direct way with their peers and their teachers. Instead of merely searching for information, applications such as bookmarking, feeds, tweeter and pinboards, digital portfolios, etc., along with the possibility of creating your own personal webpage, today’s Web gives students also the chance to create a PLE - A Personal Learning Environment. A PLE “recognizes that learning is continuing and seeks to provide tools to support that learning” (Attwell, 2007). The Individuals are responsible for the management of their own learning environment and for the selection of tools and contexts where learning will take place. Students need to acquire certain skills and competences, specific of a digital and connected society, in order to “effectively benefit from e-government, e-learning and e-health services, and participate actively in the knowledge society as co-creators, and not simply consumers, as highlighted by the European e-skills strategy” (McCormack, 2010). To only possess hard skills (that comes with experience and formal education) may not be enough to get someone a job. Besides e-skills and e-literacy competences, soft and social skills are also required. These can be practiced and enhanced in virtual environments. Digital literacy, and therefore e-skills, are transversal competences needed to every citizen. In this paper we will present the results of a case study carried out with attendees of an Erasmus Intensive Programme, which has promoted the development of digital literacies among participants. The Programme took place during 2013 summer and involved students and teachers (of teacher education and social service fields) from 3 different countries. The classes covered different tools and 12 tutors were involved. The main objectives were to provide students with information and communication technologies (ICT) skills for a digital society, namely: • Identification of students’ competencies in ICT; • Present students with different available collaboration tools by exploring the web 2.0; • Selection of specific tools to create students' personal learning environment (PLE); • Acquire necessary knowledge to master the selected tools; • Work collaboratively with the web 2.0 tools; • Establish methods for instruction and course design based on Web 2.0 (teacher education) with the goal to integrate technology enhanced learning and individual knowledge management in educational processes. At the end attendees were able to: • Master the different tools & services; • Be capable to use and select the most adequate web 2.0 tools & services; • Create and manage their PLE; • Share and to work collaboratively; • Be digitally skilled.